The Effect of Capital Intensity, Leverage, and Institutional Ownership on Tax Avoidance With Profitability as a Moderation Variable - Putri, Syavika Nurcahyani; Hariyanto, Eko; Kusbandiyah, Ani; Pandansari, Tiara (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2022)
This study aims to determine the effect of capital intensity, leverage, and institutional ownership on tax avoidance with profitability as a moderating variable. The population in this study are energy sector companies listed on Bursa Efek Indonesia for the 2017-2021 period. The sampling method used was purposive sampling, so the samples taken were 188 data that matched the criteria. The data analysis method used is the multiple regression analysis absolute difference method. The result of this study indicates that capital intensity and institutional ownership positively affect tax avoidance, while leverage does not. Profitability can strengthen the effect of capital intensity and leverage on tax avoidance, but profitability cannot moderate the effect of institutional ownership on tax avoidance. This research implies that it can be especially useful for the government so that the government can take preventive measures so that the company does not do tax avoidance.